Expression of p53 protein in premenopausal women as risk factors for breast cancer - Rashidah S,; Hairil Rashmizal Ar,; Ho, SE; Wan Mazlina Md Saad, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Mutation is known to occur before the development of various types of cancers. Mutation in p53 gene can be found in human breast cancer. The aim of the present study was to determine the correlation between p53 protein expressions with women in premenopausal age. A total of 111 breast cancer tissues were examined for p53 protein expression by IHC. The results showed that majority (36.9%; n=41/111) who were more than 41 yrs, overexpressed positive p53 (+) protein category and 2.7% (n=3/111) aged 41 yrs and less, showed less positive p53 (+) protein category. However, the Fishers exact test, indicated that, there was no significant correlation between participant’s age group with p53 protein category (χ2 (1) = 0.78; p =0.52) and no correlation strength was indicated (Cramer’s V coefficient = 0.08; p =0.37), respectively. The risk estimate showed probability of p53 (+) protein being overexpressed in the age group < 41 yrs was 0.66 times less likely compared to the age group > 41 yrs. In conclusion, with or without overexpression of p53 protein, women above 41 yrs were found to have greater risk.